PENDEKATAN PENILAIAN AUTENTIK UNTUK PEMBELAJARAN SENI BUDAYA - Cahya Yuana (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2020)
Authentic assessment is currently an issue in learning. The purpose of authentic assessment is to get a portrait of the factual competence of students. Therefore, authentic assessment is very important. Some research results indicate that many teachers reluctantly employ authentic assessments. The most often mentioned argument is due to the burdensome responsibilities of the teachers and the limited time they have. The current study attempts to affirm what authentic assessment is and how it is employed in the assessment of students’ learning in arts and culture as a subject at schools. Along with the complicated goals of arts and culture learning, authentic assessment offers a challenging issue for teachers since the subject itself aims at improving students’ attitudes. This attitude enhancement is done by providing an aesthetic experience to students. Aesthetic experience helps the achievement of the goal manifested in arts and culture practices. Therefore, teachers need to look at two features specifically constructing assessment in arts and culture learning, namely asthetic experience and arts and culture practices. The study results in the conception of an approach to authentic assessment of arts and culture learning.